The Three Kentucky Presidents : Lincoln, Taylor, Davis - Hamilton, Holman (Book collections on Project MUSE., 2003)
The three Kentucky presidents -- Abraham Lincoln, Zachary Taylor, and Jefferson Davis -- were profoundly shaped by their experiences in Kentucky, poised as it was on the border between the North and the South, the East and the Western Frontier. Holman Hamilton asserts that these leaders were personally and politically influenced by their connections to the state. The contrasting traits of western frontiersman and southern aristocrat illuminate Kentucky's heritage and affected Taylor, Lincoln, and Davis, presidents during one of America's most troubled eras. Frontier values influenced Lincoln's.